RECENT INTERANNUAL CHANGES OF STRATOSPHERIC TEMPERATURES - ヒロオカ, トシヒコ; カワヒラ, コウジ; HIROOKA, Toshihiko; KAWAHIRA, Kohji (National Institute of Polar Research, 1991)
P(論文) Recent interannual changes of zonal mean temperatures of mid and high latitudes in the lower and middle stratosphere are investigated for the period from 1980 to 1986 with the use of TIROSN and NOAA series satellite data (50-10 mb) and NMC data (300-50 mb). The zonal mean temperatures of the Southern Hemisphere lower stratosphere (300-50 mb layer) decrease in all seasons as already shown (K. KAWAHIRA and T. HIROOKA : Geophys. Res. Lett., 16,41,1989). Those of the Northern Hemisphere lower stratosphere also decrease in all seasons, although it is relatively difficult to discern such cooling in winter because of the irregular occurrence of stratospheric sudden warmings; in that case, the temperatures increase in higher latitudes while decreasing in lower latitudes. On the other hand, as for the middle stratosphere (50-10 mb layer), an increase of zonal mean temperature can be seen only in the Southern Hemisphere winter. In other seasons of the middle stratosphere of both hemispheres, significant interannual temperature changes cannot be seen from the current short analysis period. These trends found in the temperature field seem to be associated with interannual changes of general circulation of the stratosphere. Therefore, further observations of other dynamical quantities are needed in order to thoroughly understand the recent changes of stratospheric temperatures. departmental bulletin paper